Five times faster rethinking the science, economics, and diplomacy of climate change - Sharpe, Simon ca. 20./21. Jh (Cambridge University Press, 2023)
We need to act five times faster to avoid dangerous climate change. As Greenland melts, Australia burns, and greenhouse gas emissions continue to rise, we think we know who the villains are: oil companies, consumerism, weak political leaders. But what if the real blocks to progress are the ideas and institutions that are supposed to be helping us? Five Times Faster is an inside story from Simon Sharpe, who has spent ten years at the forefront of climate change policy and diplomacy. In our fight to avoid dangerous climate change, science is pulling its punches, diplomacy is picking the wrong battles, and economics has been fighting for the other side. This provocative and engaging book sets out how we should rethink our strategies and reorganise our efforts in the fields of science, economics, and diplomacy, so that we can act fast enough to stay safe